Collective Sensemaking Around COVID-19: Experiences, Concerns, and Agendas for our Rapidly Changing Organizational Lives. (August 2020) - Stephens, Keri K.; Jahn, Jody L. S.; Fox, Stephanie; Charoensap-Kelly, Piyawan; Mitra, Rahul; Sutton, Jeannette; Waters, Eric D.; Xie, Bo; Meisenbach, Rebecca J.
Uncertainty is at the forefront of many crises, disasters, and emergencies, and the COVID-19 pandemic is no different in this regard. In this forum, we, as a group of organizational communication scholars currently living in North America, engage in sensemaking and sensegiving around this pandemic to help process and share some of the academic uncertainties and opportunities relevant to organizational scholars. We begin by reflexively making sense of our own experiences with adjusting to new ways of working during the onset of the pandemic, including uncomfortable realizations around privilege, positionality, race, and ethnicity. We then discuss key concerns about how organizations and organizing practices are responding to this extreme uncertainty. Finally, we offer thoughts on the future of work and organizing informed by COVID-19, along with a list of research practice considerations and potentially generative research questions. Thus, this forum invites you to reflect on your own experiences and suggests future directions for research amidst and after a cosmology event.